Educational Intervention to Reduce Stigma Toward Person with Severe Mental Illness (SMI): A Scoping Review - Afifatul Mukaromah; Wulandari Wulandari; Dwi Indah Prasetia; Dyah Anggraeni; Ah. Yusuf (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stigma against individuals with mental health disorders remains a significant barrier to recovery, exacerbating patient conditions, fostering social discrimination, and limiting access to adequate healthcare services. Objective: This study aims to identify effective education-based interventions to reduce societal stigma toward individuals with severe mental illness (SMI) through a literature review. Method: A scoping review was conducted by searching literature in Scopus, PubMed, ProQuest, and Science Direct. Included studies (2019–2024) explored educational interventions to reduce mental health stigma. Excluded were incomplete, duplicate, review, and retracted articles Results: Of the 2,277 identified articles, eight studies met the criteria for further analysis. Findings indicate that educational methods, such as conventional psychoeducation, case studies, problem-based learning (PBL), and contact-based education, effectively reduce stigma against individuals with SMI. All interventions focused on improving mental health knowledge. Educational strategies varied based on target audiences, delivered through offline approaches (lectures, case studies, PBL) and online methods (educational videos). Combining online and offline approaches further enhanced knowledge and attitudes toward individuals with SMI. Conclusions: Several educational strategies have been developed to address stigma, whether through online education, face-to-face offline interactions, contact with individuals with mental illnesses, or a combination of these methods. By implementing the right educational methods, stigma toward individuals with (SMI) can be addressed across various target groups.